Industrial development - Ruane, Frances (Statistical and Social Inquiry Society of Ireland, 1983)
The recent review of industrial policy is the first major industrial policy review since the gradual shift in economic policies some twenty years ago from promoting import substituting native industries by tariffs and controls on foreign investment, to promoting exports and direct foreign investment by capital grants and tax holiday. The decision to change dramatically the focus of industrial policy was made by Lemass in response to the failure of existing policies to solve both sectoral and economy-wide problems: the lack of any sustained growth in Irish industry and its poor prospects, given increasing, if low, import penetration; rising balance of payments deficits; high rates of unemployment and emigration, etc. Ironically, it was in response to broadly similar problems that the current review of policies by the National Economic and Social Council (NESC) was requested. The NESC has produced five reports on industrial policy, and I propose to confine my remarks to the main, and most controversial report, namely, A Review of Industrial Policy, hitherto referred to as the Telesis Report.
Symposium on Industrial Policy in Ireland
Read before the Society, 2 December 1982
Keywords: Irish industrial development; Irish industrial policy; A Review of Industrial Policy; Telesis report; 314.15